The Effect Of Human Resource Quality And Employee Loyalty On Employee Performance Through Employee Competence At The Batubara Regency Population And Civil Registration Office - Elisa Alsen Pasaribu; Yohny Anwar (International Journal of Management, Economic and Accounting, 2025)
This study aims to determine the influence of the influence of human resource quality and employee loyalty on employee performance through employee competence at the Batubara Regency Population and Civil Registration Office. In this study, a quantitative approach based on statistical information is used. The population In this study is all employees at the Batubara Regency Population and Civil Registration Office which totals 120 employees. The sampling technique in this study uses the slovin formula so that the number of samples in this study was obtained as many as 92 respondents. The data analysis technique used descriptive statistical analysis and Partial Least Square (Smart-PLS). The results of the study show that: The Quality of Human Resources (X1) has a positive effect (2.810>1.98729) and significant (0.006< 0.05) on Employee Performance (Y). Employee Loyalty (X2) has a positive effect (3.404>1.98729) and significant (0.001< 0.05) on Employee Performance (Y). The quality of Human Resources (X1) has a positive effect (6.639>1.98729) and significant (0.000< 0.05) on Employee Competence (Z). Employee Loyalty (X2) has a positive effect (3.634>1.98729) and significant (0.000< 0.05) on Employee Competence (Z). Employee Competency (Z) has a positive effect (5.551>1.98729) and significant (0.000< 0.05) on Employee Performance (Y). The quality of Human Resources (X1) has a positive effect (4.354>1.98729) and significant (0.000< 0.05) on Employee Performance (Y) through Employee Competency (Z). Employee Loyalty (X2) has a positive effect (3.114>1.98729) and significant (0.002< 0.05) on Employee Performance (Y) through Employee Competency (Z) at the Coal Regency Population and Civil Registration Office.